ANALISIS DINAMIKA EKONOMI-SOSIAL PADA DISTRIBUSI SET TOP BOX TV DIGITAL DI PROVINSI BANTEN - Riyanto, Japar; Fazarudin, Arif; Adiana, Bintang Dwi; Sukron, Koid Jalal; Nursalim, Nursalim; Laksana, April (Bussman Journal : Indonesian Journal of Business and Management, 2023)
There are problems related to the distribution and use of Set Top Box (STB) in the Banten Province. As part of the national television digitalization program, the government has encouraged the public to switch from analog to digital TV by using STB. There are several obstacles in the distribution and use of STB in the Banten Province, such as differences in income levels and infrastructure availability, lack of socialization and information, market competition, and varying needs and preferences of the community. This results in uneven distribution and use of STB throughout the Banten Province. By identifying these social factors, it is hoped that the government and broadcasting operators can develop more effective and efficient strategies to increase the use of STB throughout the Banten Province. The purpose of this study on the social dynamics of STB distribution and use in the Banten Province is to identify the social factors that affect the distribution and use of STB in the region. This study aims to provide a better understanding of the social dynamics of STB distribution and use in the Banten Province, and thus provide information and input for the government and broadcasting operators in formulating policies and strategies for more effective and efficient STB distribution and use in the region. The results of this study suggest that to address these social dynamics, the government and broadcasting operators need to take various measures, such as improving socialization and information about STB, providing price subsidies for STB for low-income communities, and building adequate infrastructure to support the distribution of STB throughout the Banten Province. With these efforts, it is hoped that the distribution and use of STB can become more equitable throughout the Banten Province, and the public can enjoy the benefits of digital television technology